Pengaruh dan Perancangan Sistem Informasi Manajemen dalam Kegiatan Bisnis Online: Studi Kasus pada Penjualan Pakaian serta Penjualan, Pembelian, dan Inventori Kantor GM Tupperware - Muhamad Hanafi; Heidiani Ikasari, Ines (Shofanah Media Berkah, 2023)
This research aims to analyze the impact of Management Information Systems (MIS) on online business activities and design an MIS for the sales and management of sales, purchases, and inventory at GM Tupperware office. The use of information technology and the internet has brought significant changes to the business world, including online business. Management Information Systems play a crucial role in efficiently and effectively managing online business operations. This research will employ a qualitative approach with a case study on clothing sales and the management of sales, purchases, and inventory at GM Tupperware office. The study will result in the design of an MIS that can assist in managing clothing sales as well as sales, purchases, and inventory at GM Tupperware office. The implementation of an effective MIS will enhance operational efficiency, improve decision-making, and enhance overall business performance